Mosques as a Platform to Address the Issue of the Anti-Hadith Ideology - Ghazali, Mohd Al’ikhsan (Al-Bayān, 2016)
In Malaysia, the authorities have taken a number of steps to prevent the anti-Hadith movement. Various parties, especially the religious authorities at federal and state levels, have united to try to resolve the anti-Hadith issue, and activities such as weekly talks and lectures have been organized by mosque institutions to halt the spread of this ideology. The objective of this study is to investigate whether any significant correlation can be seen between attendance at the programs of the mosque and the influence of the anti-Hadith. This quantitative study involved the distribution of questionnaires that included anti-Hadith related questions to 800 participants in order to gather demographic data as well as information regarding their attendance of mosque lectures. A detailed analysis between the interest of those who took part in programs at mosques and the influence of anti-Hadith had a significant impact. The results indirectly prove that Muslims who frequented the mosques were safe from the influence of the anti-Hadith movement. Consequently, it can be said that the spiritual teaching carried out in mosques has succeeded in preserving the faith of Muslims. This study highlights the fact that such spiritual teaching can be one of the main factors to help Muslims to avoid dangerous ideologies.